2019
DOI: 10.1016/j.ebiom.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

MiR-338-5p promotes metastasis of colorectal cancer by inhibition of phosphatidylinositol 3-kinase, catalytic subunit type 3-mediated autophagy pathway

Abstract: Background In our preliminary screening, expression of miR-338-5p was found to be higher in primary colorectal cancer (CRC) with metastasis. The autophagy related gene- phosphatidylinositol 3-kinase, catalytic subunit type 3 (PIK3C3) appeared to be targeted by miR-338-5p. Here, we provide solid evidence in support of PIK3C3 involved in miR-338-5p related metastasis of CRC in vitro and in vivo . Methods The potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…This indicated that kindlin-2 inhibited cell migration by inducing autophagy. Similar results have been reported in other types of tumors, including hepatocellular carcinoma, renal cell cancer, and colorectal cancer (36)(37)(38). The present results also provide new evidence for the role of autophagy in the migration of cervical cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…This indicated that kindlin-2 inhibited cell migration by inducing autophagy. Similar results have been reported in other types of tumors, including hepatocellular carcinoma, renal cell cancer, and colorectal cancer (36)(37)(38). The present results also provide new evidence for the role of autophagy in the migration of cervical cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…AlkB homolog 5 (ALKBH5) is an N6‐methyladenosine (m6A) eraser protein. And, it inhibited autophagy of epithelial ovarian cancer through miR‐7 and regulated ovarian cancer proliferation and invasion via B cell lymphoma 2 (Bcl‐2) . MiR‐338‐5p promotes metastasis of colorectal cancer by inhibition of phosphatidylinositol 3‐kinase, catalytic subunit type 3‐mediated autophagy pathway .…”
Section: Introductionmentioning
confidence: 99%
“…And, it inhibited autophagy of epithelial ovarian cancer through miR-7 and regulated ovarian cancer proliferation and invasion via B cell lymphoma 2 (Bcl-2). 98 MiR-338-5p promotes metastasis of colorectal cancer by inhibition of phosphatidylinositol 3-kinase, catalytic subunit type 3-mediated autophagy pathway. 99 Pancreas ductal adenocarcinoma (PDAC) is one of the most common gastrointestinal malignancies.…”
mentioning
confidence: 99%
“…The roles of ncRNAs such as lncRNAs [ 133 , 134 ], circRNAs [ 73 , 135 ], and miRNAs [ 133 , 136 ] have been recognized in cancer metastasis and autophagy. Figure 3 summarizes the potential roles of ceRNA-mediated autophagy in modulating metastasis.…”
Section: Cerna-mediated Autophagy and Metastasismentioning
confidence: 99%